Adherence Rate, Barriers to Attend, Safety, and Overall Experience of a Remote Physical Exercise Program During the COVID-19 Pandemic for Individuals After Stroke - Torriani-Pasin, Camila; Palma, Gisele Carla dos Santos; Makhoul, Marina Portugal; Antonio, Beatriz de Araujo; Lara, Audrea R. Ferro; Silva, Thaina Alves da; Caldeira, Marcelo Figueiredo; Júnior, Ricardo Pereira Alcantaro; Domingues, Vitoria Leite; Freitas, Tatiana Beline de; Mochizuki, Luis (Frontiers in Psychology, 2021)
Introduction: Government actions to deal with the consequences of the COVID-19 pandemic caused different levels of restriction on population mobility. The need to continue offering physical exercise to individuals after stroke became urgent. However, these individuals may have barriers to adhere programs delivered remotely. There is a lack of evidence related to adherence, attendance, safety, and satisfaction of remote exercise programs for this population. Objective: To evaluate adherence and barriers to attend a remote physical exercise program for individuals after stroke. We aimed (a) to identify adherence and attendance rate of the remote physical exercise program; (b) to identify the safety of a remote physical exercise program and, (c) to identify the overall experience to participate in a remote program. Materials and Methods: This is a longitudinal study, including third-six stroke survivors who already attended a face-to-face physical exercise program prior the COVID-19 pandemic. The remote physical exercise program included two weekly sessions, during 22 weeks, totalizing forty-four sessions, which were delivered asynchrony via recorded video sessions. As outcome measures, we performed two questionnaires (via weekly telephone calls) to identify attendance, barriers, safety, and overall experience related to the program. Results: Adherence rate was 86,9%. Attendance rate was 19,8 sessions in total (108,3 minutes/week). The main barriers for lower attendance rate were: Lack of motor skills and physical fitness to workout in 80 reports (20.6%), followed by no exercise companion in 44 reports (11.3%). The remote physical program has shown to be safe and the overall experience was positive from participants' and family members’ perspectives. Conclusion: Although the adherence rate was high, the attendance rate was low on the remote physical exercise program. The main barriers to attending the program remotely reflect the need of tailoring individually an asynchrony mode of delivering the sessions to individuals after stroke. Our results also indicate how the COVID-19 impacted the health conditions of stroke survivors. The program was safe and the overall experience indicated a change in the mental, physical, and social health of individuals after stroke and their family members